Approaches of De novo Assembly, Annotation and RNA-Seq Profiling in Forest Tree Improvement: A Review - Fatima, Tanzeem; Srivastava, Ashutosh; Hanur, Vageeshbabu S.; Srinivasa Rao, M. (Indian Forester, 2021)
Transcriptome analysis (RNA-seq) using next generation sequencing has allowed the researchers to simultaneously identify gene expression dynamics and differential gene expressions. This technique has a better approach to understand the biological functions of plants/trees. RNA-seq also gives information that how genes are regulated and the assembled sequence data help in designing biomarkers for unknown or new species. In forestry species, it has enabled the study of how gene expression changes in several trees due to stress or other factors. Therefore, RNAseq analysis plays a key role in advancing genomic and molecular biology research in forest trees. Due to lack of deep genomic background of forest trees, transcriptomes for most species need to be assembled de novo i.e., without reference. In the present review, we have reported and assembled reference RNA-seq data available for tropical and temperate forest tree species for the first time. This article also focuses on the terminologies and steps used for whole transcriptome analysis system, since from the collection of plant material, to extraction of total RNA, library preparation, transcripts, coding sequences, unigenes, functional annotation, gene ontology, differential expressed genes (DEGs), gene expression values and functional metabolic pathways analysis.